PANDA Type Four-Core Fiber With the Efficient Use of Stress Rods - Yi Yang; Jitao Gao; Songnian Fu; Xinben Zhang; Ming Tang; Weijun Tong; Deming Liu (IEEE Photonics Journal, 2019)
We design a panda type four-core fiber with a comparable optical property of the polarization maintenance single mode fiber (PM-SMF) and can support 8 non-polarization-degenerate eigenmodes with a birefringence of approximate 3.24 × 10−4 over the wavelength range from 1288 to 1630 nm. In particular, only four stress rods are efficiently used to achieve the PM characteristics for each core, in comparison with traditional design of panda type PM-SMF. Meanwhile, we identify that the optimal configuration of stress rods can not only enhance the birefringence, but also further suppress the crosstalk (XT) between two primary eigenstate of polarization (ESOP) arising in adjacent cores, although the corresponding XT at secondary ESOP remains unchanged. Moreover, our numerical results show that both chromatic dispersion (CD) together with mode field diameter (MFD) and the bending sensitivity are consistent among four cores. We believe that such specialty multi-core fiber is ideal for compact and cost-effective fiber-optic gyroscope (FOG) application, besides the potential in the MIMO-free spatial division multiplexing (SDM) interconnection.